2021
DOI: 10.1111/1753-6405.13092
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐methods evaluation of an urban Aboriginal diabetes lifestyle program

Abstract: Objective: The objective of this study was to evaluate an Aboriginal‐led diabetes lifestyle program catering to urban Aboriginal people in an Aboriginal organisation. Methods: Mixed‐methods study that employed routinely collected physiological data and audio‐recorded focus group sessions. Physiological data were analysed using a multi‐level model to account for participant clustering. Qualitative data were subject to thematic analysis. Results: Participants were overwhelmingly positive about the program. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Our minimally tailored text‐messages were considered culturally acceptable, similar to findings from an Aboriginal infant feeding mHealth program with minimal tailoring 13 . Despite the text‐messages being automated, they were perceived as personal and caring by participants; and the ability to save, re‐read and share text‐messages was valued; also reported in another Aboriginal study involving a text‐message component 11 …”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Our minimally tailored text‐messages were considered culturally acceptable, similar to findings from an Aboriginal infant feeding mHealth program with minimal tailoring 13 . Despite the text‐messages being automated, they were perceived as personal and caring by participants; and the ability to save, re‐read and share text‐messages was valued; also reported in another Aboriginal study involving a text‐message component 11 …”
Section: Discussionmentioning
confidence: 91%
“…The other lifestyle factors of fruit, sugary drinks, alcohol, physical activity and smoking showed potentially promising results, and warrant further investigation with a larger study to determine efficacy. This would add to the limited literature regarding health text‐message programs for Aboriginal people, such as the Too Deadly for Diabetes study which reported significant improvements in HbA1c, systolic blood pressure and weight loss at 10 weeks after an intensive multi‐factorial intervention including meal plans and an online cooking program; tracking of weight loss, foods eaten and exercise into personalised diary; flexible exercise program; YouTube videos on motivation, barriers and exercise sessions; text‐messages; and face‐to‐face weekly group sessions 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations